Russlands Arlington? Der Föderale Militärische Gedenkfriedhof bei Moskau - Gabowitsch, Mischa (RIHA Journal, 2017)
Opened in 2013, the Federal Military Memorial Cemetery near Moscow is Russia’s new national cemetery. Providing for the interment of political as well as military leaders, it is to supplant the Kremlin Wall as the country’s prime burial site. Initially modeled after the Arlington National Cemetery and designed as a landscaped park, the site was eventually built as a monumental complex dominated by bronze statues. Plans to let common soldiers be buried here next to decorated heroes were abandoned. This article analyzes the rival designs and the conflict surrounding the site’s construction. It also proposes a typology of national cemeteries. More than Arlington, the Federal Military Memorial Cemetery resembles heroes‘ cemeteries in countries influenced by the ideas of revolutionary liberation struggles and socialist realism.